Digitalisasi Kitab Nadham Batu Ngompal Karya TGKH. Muhammad Zainuddin Abdul Madjid Berbasis OPF Flipbook - Bahtiar, Hariman; Sutriandi, Aswian Editri; Djamaluddin, Muhammad (Fakultas Teknik Universitas Hamzanwadi, 2020)
TGKH. Muhammad Zainuddin Abdul Madjid is one of the charismatic figures and scholars who came from Lombok Island. Many works have been produced by the purchase during his life, to be used as a guide for students and pilgrims who buy and lead. Maulana Shaykh's works still use conventional media in the form of paper. With this conventional media, mostly with frequent use or improper placement, it can make the media become damaged. The use of technology to preserve and preserve the works of charismatic figures and great scholars such as TGKH. Muhammad Zainuddin Abdul Madjid is very important. One of the works of purchase is Nazam Batu Ngompal, Nadham